Effects of Supplemented Growth Promoters on Performance and Intestinal Morphology in Broilers Reared under Different Stocking Densities - Altaf,MT (2019)
ABSTRACT The aim of the present study was to investigate the influence of different growth promoters on broiler performance and intestinal morphology reared under various stocking densities. A total of 900 day old (Ross-308) straight run broilers were randomly divided into fifteen treatment groups according to a completely randomized design. A 5 × 3 factorial arrangement of treatment was employed. Treatments were consisted of four growth promoters (antibiotics, prebiotics, probiotics, and symbiotics) and a control group with three stocking densities (0.046, 0.056, 0.065m2). Each treatment was replicated 6 times with 10 birds in each. Regarding growth performance, feed intake (p=0.0008), body weight (p=0.0085) and feed conversion ratio (p=0.0001) were improved with the supplementation of symbiotic in the diet whereas lower body weight was noted in the control group. In terms of intestinal morphology, villus height (p=0.0011) and villus to crypt ratio (p=0.0001) were significantly higher in the symbiotics treatment groupas compared to the control group. Moreover, birds reared under 0.065m2 stocking density showed improvement in body weight, feed conversion ratio and livability as compared to the other treatment groups. It can be concluded that the supplementation of symbiotics in the diet of commercial broiler reared under 0.065m2 stocking density had a positive influence on overall growth performance and intestinal morphology.